Perseptive of Environment in Hindu Science and Culture - Subash Chandra Dash (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
The environmental awareness growing today is a reaction to the environmental chaos caused by the selfish technological achievements. Today, people are actually suffering from problems such as pollution, Population growth, and imbalance in environmental cycles etc. Therefore, humanists of 20th cen. have anxiously stated thinking for such problems, with various dimensions. Param?tm? is nirgu?a (without any quality), akha??a (whole), advaita(only one), nitya (ever existing), nirmala (pure), svayamprak??a (self –luminescent), satya (Truth) and jñ?na svarupa(wisdom incarnate). Puru?a is used as his synonym.The energy (?akti) emanating from the Parm?tm? is the nature (prak?ti) . First this energy is avyakta (unmanifested). Then it becomes mahat( effervescent). Next it attains ahamk?ra (inexorability). And it results in ?abda tanm?tr?s (sound etc. qualities) and turns tangible into the ?k??a pa?cha mah?bhutas (sky etc. five elements). Of these five, water becomes all-pervading. And innumerable brahm??das (universal eggs or universes in spherical shape) begin floating on that water. This is the process of initial creation.